ETHNOBOTANICAL AND ETHNOVETERINARY IMPORTANCE OF PLANTS OF SCRUB AREAS OF DACHIGAM NATIONAL PARK, JAMMU AND KASHMIR, INDIA - MALIK, ARIF YAQOOB; SINGH, D.P (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The rich plant diversity of mountains has been used by the indigenous people for thousands of years as health-care remedies. A study on the important plant communities of scrub ecosystems of Dachigam National Park was carried out with the special aim of enlisting the ethnobotanical, and ethnoveterinary uses of plants being used by the people of the area. Methods: Data were collected by visual appraisal approach, rapid rural approach, and questionnaire methods coupled with group meetings and field discussions. Results: Data collected from the present investigation indicate that 59 plants belonging to 33 families with Rosaceae, the dominant family, were exclusively used for ethnobotanical purposes and 10 plant species belonging to 8 families were having ethnoveterinary use. These species include 14 medicinal species, 10 vegetable species, 10 with edible species, 6 fodder species, 6 species used as tea substitutes, 3 species for menstrual problems, 3 species used for religious ceremonies, 2 species used for chutney, 2 art and craft species, and 1 species used for ornamental, fuelwood, and agricultural tools each. Conclusion: The people of the area are exclusively dependent on medicinal plants using traditional knowledge that provides them with the best therapeutic and economic benefits. Such traditional knowledge could be valuable for developing local and regional conservation strategies for these fragile ecosystems. There is an urgent need to thoroughly analyze the secondary metabolite properties of such plants to validate their authenticity in the local health-care systems.